The community participation in the case detection of the suspect pulmonary tuberculosis in the district of Tanah Datar, West Sumatera, Indonesia - Sabri, Rika (Universiti Kebangsaan Malaysia, 2011)
Pulmonary tuberculosis is the major infectious diseases that cause death in Indonesia. Indonesian government’s efforts to cope with this disease are to follow the WHO recommendation to use the DOTs strategy. The weakness of this strategy is DOTs socialization has not reached all health centers, government and private hospitals so that the finding of new cases is still very low. Introduced an alternative model is the partnership of educational institutions, health services and communities, through community empowerment in the early detection of TB cases. This model was named “Corong Segitiga sehat Model.” The purpose of this study was to see community participation in trials that proved the model of the household contact person coverage checked him into the clinic. Quantitative and qualitative research methods with experimental research design that uses one-group pre-post test. The results showed the formation of partnerships with the model PPTB group after 1 month of training provided by educational institutions and health centers, patients with detectable BTA (+) as many as 9 people, as many as 14 people with suspected tuberculosis. These data supported the statement that the results of the training cadre will strengthen our selves for the more daring cadres advised people to check their household contact him to health center. Involve partnerships with community participation is one key to effective implementation of the model to detect new cases of tuberculosis. It is recommended for local governments actively participate as one component of a healthy funnel triangle, because of the influence of local government to increase community larger.